Componentes da produção e produtividade de milho cultivado sobre biomassa de forrageiras tropicais - Diniz , Leomar Custódio (2021)
The integration of crops and livestock (ILP) is one of the alternatives for the mitigation of greenhouse gases (GHG), this system has been growing in the last few years, due to a greater turnover of capital per hectare. However, some studies report that there may be a loss of productivity in the adoption of this system. With this, the objetive was to evaluate the effect of three grasses as cover plants on the components of the production and productivity of the corn crop in the ILP system. The research was carried out in a system of crop and livestock integration with a focus on the production of grain. The treatments consisted of sowing the maize in the biomass of three species of grasses of the Urochloa brizantha genus, using the cultivars MG5, MG4 and MG13-Braúna or without vegetation cover (witness). Residual feed biomass and morphological characteristics of maize and components of maize production and productivity were assessed. There was greater productivity in biomass and organic matter (MO) (P<0.05) to cultivate MG5, while the cultivar MG4, MG13 presented similar and intermediate production. The area without vegetation cover was the one that showed the lowest productivity, both for biomass and MO. No difference was found between treatments for the final plant stand (LRU), number of ears per plant (NESP), length of cob without straw (COMP), number of rows of grains (NFG), number of grains per row (NGF), weight of straw-free cobs (PSP), weight of the cob grains (PGE) and for grain production per hectare (P>0,05). the use of cultivars of Urochloa brizantha MG4; MG5 and MG13 increase the productivity of biomass to cover the soil in the ILP system without affecting the productivity of corn grains, and the cultivar MG5 presented greater cover of the soil.